2003
DOI: 10.1136/bmj.327.7420.901
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and body composition of 18 year old men according to duration of breast feeding: birth cohort study from Brazil

Abstract: Objective To assess the association between duration of breast feeding and measures of adiposity in adolescence. Design Population based birth cohort study. Setting Pelotas, a city of 320 000 inhabitants in a relatively developed area in southern Brazil. Participants All newborn infants in the city's hospitals were enrolled in 1982; 78.8% (2250) of all male participants were located at age 18 years when enrolling in the national army. Main outcome measures Weight, height, sitting height, subscapular and tricep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
3
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 15 publications
12
115
3
7
Order By: Relevance
“…13,27,[33][34][35][36][37][38] The findings of the current study showed that exclusive breastfeeding for the first 6 months of life reduced the risk of overweight at 6 and 12 months of age, but was not found to have any subsequent positive effect from 1 to 5 years of age. The positive link between long-term breastfeeding and lower rates of overweight could operate through several possible biological mechanisms.…”
Section: Discussioncontrasting
confidence: 42%
“…13,27,[33][34][35][36][37][38] The findings of the current study showed that exclusive breastfeeding for the first 6 months of life reduced the risk of overweight at 6 and 12 months of age, but was not found to have any subsequent positive effect from 1 to 5 years of age. The positive link between long-term breastfeeding and lower rates of overweight could operate through several possible biological mechanisms.…”
Section: Discussioncontrasting
confidence: 42%
“…Although the effects of the complementary foods introduction contributing to childhood obesity have not been fully estimated, the duration and exclusivity of breastfeeding seems to be a protective factor in some studies, [22][23][24] but not all. 25 Our data seem to indirectly support that prolonged exclusivity of breastfeeding might help maintain a normal body weight among infants in the earlier years of life.…”
Section: Macrosomia and High Weight-for-height Z Yu Et Alsupporting
confidence: 51%
“…However, other studies have failed to detect similar effects. 11,20,25 The discrepant results obtained in studies evaluating the association between breastfeeding and child/adolescent obesity may be due to differences in study design, sample size, and adjustment -or lack of such -for potential confounders, especially birthweight, maternal obesity, and socioeconomic status. Different hypotheses have been proposed for the protective effects of breastfeeding.…”
Section: Introductionmentioning
confidence: 85%